Privacy concern on social network sites: the role of protection motivation, trust and risk - Salleh, Norsaremah; Hussein, Ramlah; Mohamed, Norshidah; Abdul Karim, Nor Shahriza; Ahlan, Abdul Rahman; Aditiawarman, Umar (2012)
For someone to be acknowledged in Social Network Sites (SNS), he/she needs to reveal his/her identity. How far personal information SNS users want to disclose is determined by their assessment of threat and ability to control the information. By adopting protection motivation theory (PMT) as a framework, incorporated with trust and risk factor, this study revealed trust on SNS and perceived benefits influenced information disclosure behaviour. Surprisingly, privacy concern and perceived risk were found not to be related to information disclosure behaviour. Using self-administered questionnaire, 486 undergraduate students from five different universities in Malaysia were involved in this study.